Answer:
![x=(-5-√(57) )/(2)\ or\ x=(-5+√(57) )/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nut80sziv9jud2gnkkkryy38ga48s3n146.png)
Explanation:
Given:
The equation to solve is given as:
![x^2=-5x+8](https://img.qammunity.org/2020/formulas/mathematics/middle-school/e6gz840zcsfkt60m8qy1xxr5uslctxtm69.png)
Rearrange the given equation in standard form
, where,
are constants.
Therefore, we add
on both sides to get,
![x^2+5x-8=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vzb0bww5r5t0p3ezijo8nez0v2o9tww2au.png)
Here,
![a=1,b=5,c=-8](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xgb90ww7xkv8hbz0bcut5topsbbnzkyrjd.png)
The solution of the above equation is determined using the quadratic formula which is given as:
![x=(-b\pm √(b^2-4ac))/(2a)](https://img.qammunity.org/2020/formulas/mathematics/high-school/ab45cdhbeliwcal3naam0rctuj1s2ka8cv.png)
Plug in
and solve for
.
![x=(-5\pm √(5^2-4(1)(-8)))/(2(1))\\x=(-5\pm √(25+32))/(2)\\x=(-5\pm √(57))/(2)\\\\\\\therefore x=(-5-√(57) )/(2)\ or\ x=(-5+√(57) )/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/v9de3djye6hn76222gir0htzbujtqhfjsm.png)
Therefore, the solutions are:
![x=(-5-√(57) )/(2)\ or\ x=(-5+√(57) )/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nut80sziv9jud2gnkkkryy38ga48s3n146.png)